Commodification of Tibetan culture by socially mediated place branding - Miao, Yuanke (2022)
This study analysed the tourism-oriented place branding videos of a state- controlled Tibetan celebrity published via social media. The analysis applied multimodal discourse analysis as the methodological tool to examine the features and settings to discursively construct Tibetan culture on popular digital media. Then this study connected them to explain how the video producers balance the traditional elements and practices with modern identities. The data set consisted of two official tourism promotional videos and five vlogs of Ding Zhen (丁真) from Bilibili and TikTok. The multimodal analysis focused on several modes (clothing, objects, activities layout, sound effects, and visual effects) in three different settings; the natural environment, modern city, and Ding Zhen’s hometown. The study found that Tibetan traditional elements were strongly associated with the natural environment and hometown setting in official tourism promotional videos, while modern features were emphasized in vlogs. Both Tibetan traditional identity and modern Chinese identity were highlighted in Ding Zhen’s videos. However, some stereotypes like the masculinity of Tibetan men were reinforced by modern activities, while the religious part was weakened and hidden.